(untitled) (Revista Argentina de Musicología, 2012)
In the musical and artistic scene of Mexico, the 1960s and beginning of the 1970s constitute a singular moment of reconsidering the future and a critical questioning of the past. In this article we focus on Mario Lavista’s first decade as a composer, for his music has played a key position in illustrating aspects that guided the musical profile of the second half of the twentieth-century in Mexico. We analyze the way in which Lavista relates to American and European avant-garde trends. We focus on his early works, in which the composer uses atonal languages, experiments with extended techniques, and reconfigures the performer’s role. These actions served as differentiation strategies that fed the anti-nationalist discourse that surrounded the reception of Lavista’s music. The detailed study of the composer’s first decade prevents it from falling behind other historical accounts of his oeuvre. Even though it could be said that Lavista entered a different stage after this time, many of the ingredients that constitute his language today were already present in that initial compositional period.